Prevention of relapse after allogeneic hematopoietic cell transplantation by donor and cell source selection - Fleischhauer, Katharina (Bone Marrow Transplant, 2018)
Allogeneic hematopoietic cell transplantation (HCT) is the most established form of cancer immunotherapy and has been successfully applied for the treatment and cure of otherwise lethal neoplastic blood disorders. Cancer immune surveillance is mediated to a large extent by alloreactive T- and natural killer (NK)-cells recognizing genetic differences between patient and donor. Profound insights into the biology of these effector cells has been obtained over recent years and used for the development of innovative strategies for intelligent donor selection, leading to improved graft-versus-leukemia effect without unmanageable graft-versus-host disease. The cellular composition of the stem cell source plays a major role in modulating these effects. This review summarizes the current state-of the-art of donor selection according to HLA, NK -alloreactivity and stem cell source.